1997
DOI: 10.1111/j.1467-2494.1997.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Vapour pressure of a fragrance ingredient during evaporation in a simple emulsion

Abstract: The phase diagram water, phenethyl alcohol and laureth 4 was determined and the variation of the vapour pressure of the alcohol was determined during evaporation using gas chromatographic head-space analysis. The phase changes during evaporation were estimated from the phase diagram and compared to the appearance of the emulsion using optical microscopy. The transfer of the fragrance ingredient between different phases during the process was estimated and its measured vapour pressures compared to those calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The evaporation process of the fragrance from the model system is directly related to its equilibrium vapour pressure at the specific physical state [18]. Friberg et al [17] compared the vapour pressure during free evaporation with that of an equilibrated fragrance emulsion, and found that they are almost identical to each other. Recently the vapour pressure of a variety of fragrance compounds in different amphiphilic association structures has been determined by our group [19±23], among which the systems of the fragrance combined with the nonionic surfactant [19,23] are of particular interest, as nonionic surfactants are neither toxic nor irritant, and thus widely used in cosmetic products [8].…”
Section: Introductionmentioning
confidence: 99%
“…The evaporation process of the fragrance from the model system is directly related to its equilibrium vapour pressure at the specific physical state [18]. Friberg et al [17] compared the vapour pressure during free evaporation with that of an equilibrated fragrance emulsion, and found that they are almost identical to each other. Recently the vapour pressure of a variety of fragrance compounds in different amphiphilic association structures has been determined by our group [19±23], among which the systems of the fragrance combined with the nonionic surfactant [19,23] are of particular interest, as nonionic surfactants are neither toxic nor irritant, and thus widely used in cosmetic products [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that the present formulations in the form of colloidally solubilized systems may remedy this problem. Our earlier contributions (12)(13)(14)(15) have demonstrated that a simple emulsion system may keep the vapor pressure of a single fragrance compound, phenethyl alcohol (PEA), approximately constant during the period of water evaporation (-30 min) from a skin lotion and revealed the usefulness of phase diagrams to elucidate changes during evaporation.…”
mentioning
confidence: 99%
“…3. These calculated pressures have been compared [18] to those actually measured from the emulsion. The agreement is very good (Fig.…”
Section: Evaporation Trajectoriesmentioning
confidence: 99%